Nucleotide Sequence at the Binding Site for Coat Protein on RNA of Bacteriophage R17 - Bernardi, Alberto (1972)
The binding of a few molecules [1-6] of RNA bacteriophage coat protein to 1 molecule of RNA represses in vitro translation of the RNA synthetase cistron. Digestion of the complex, R17 coat protein-R17 RNA, by T1 RNase yields an RNA fragment bound to the coat protein. The nucleotide sequence of this fragment (59 residues) reveals that it contains the punctuation signal between the coat protein and RNA synthetase cistrons, suggesting that this is the site on the RNA where the coat protein acts as a translational repressor.